Non-overlapping domain decomposition methods for three-dimensional cardiac reaction-diffusion models and applications - Stefano Zampini (Mathematical Sciences, 2011)
Recent advances in biotechnology and the availability of ever more powerful computers have led to the formulation of increasingly complex models at all levels of life sciences, in particular of cardiac electrophysiology. Multiscale modeling of the bioelectric activity of the heart, taking into account macroscopic (fiber architecture and anisotropy) and microscopic (cellular) features of the tissue, aim to develop predictive tools for future drug design and patient-specific therapies, using detailed and efficient three-dimensional solvers for the governing equations of tissue electrophysiology.